Do individual psychological characteristics predict induction and generalization of nocebo and placebo effects on pain and itch? - Weng, Lingling; van Laarhoven, Antoinette I. M.; Peerdeman, Kaya J.; Evers, Andrea W. M. (Frontiers in Psychiatry, 2022)
Background Nocebo and placebo effects, i.e., adverse or beneficial treatment effects, respectively, putatively due to expectancies can modulate pain and itch. These effects can generalize within the pain or itch modality. Predicting the induction and generalization of these effects can be helpful in clinical practice. This study aims to investigate whether psychological characteristics related to the fear-avoidance model predict the induction and generalization of nocebo and placebo effects on pain and itch in young healthy participants. Methods Data from two previous experiments were analyzed. In Experiment 1, we induced nocebo and placebo effects on heat pain and tested generalization to pressure pain and to cowhage-evoked itch (n = 33 in a nocebo group, n = 32 in a placebo group). In Experiment 2, we induced nocebo effects on cowhage-evoked itch and tested generalization to mechanical itch and to mechanical touch (n = 44). Potential predictors were anxiety- and stress symptoms, attention to pain/itch, and pain/itch catastrophizing. Multiple regression analyses were performed. Results For nocebo effects, none of the individual psychological characteristics significantly predicted induction of nocebo effects nor their generalization. For placebo effects, only less stress symptoms, lower attention to pain, and higher pain catastrophizing weakly predicted a stronger generalization of placebo effects from heat pain to pressure pain. Conclusion The tested psychological characteristics may not play an important role in the induction and generalization of nocebo and placebo effects in healthy individuals. However, firm conclusions cannot be drawn with the current sample. Future studies should validate findings in larger and more diverse samples.